Hadith #2524 - Sunan Abi Dawud - Abu Ayyub al-Ansari; Amr bin 'Uthman عمرو بن عثمان بن عفان; Ibrahim bin Musa al-Razi al-Fara' إبراهيم بن موسى الرازي الفراء; Muhammad bin Harb al-Wasti محمد بن حرب بن حرمان النشائي; Yahya bin Jabir al-Tai'i يحيى بن جابر الطائي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) made a brotherhood between two men, one of whom was killed (in Allah’s path), and a week or thereabouts later the other died, and we prayed at his funeral). The Messenger of Allah (ﷺ) asked: What did you say? We replied: We prayed for him and said: O Allah, forgive him, and join him to his companion. The Messenger of Allah (ﷺ) said: What about his prayers since the time the other died, and his fasting since the time the other died–the narrator Shu’bah doubt
Grade: Sahih

Hadith #2932 - Sunan Abi Dawud - Amr bin 'Uthman عمرو بن عثمان بن عفان; Muhammad bin Harb al-Wasti محمد بن حرب بن حرمان النشائي; Salah bin Yahya bin al-Mqdam صالح بن يحيى بن المقدام; Yahya bin Jabir al-Tai'i يحيى بن جابر الطائي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: When Allah has a good purpose for a ruler, He appoints for him a sincere minister who reminds him if he forgets and helps him if he remembers; but when Allah has a different purpose from that for him. He appoints for him an evil minister who does not remind him if he forgets and does not help him if he remembers.
Grade: Sahih

Hadith #4299 - Sunan Abi Dawud - Abd al-Whab bin Njd'h عبد الوهاب بن نجدة; Abu Salma al-Himsi Suliaman bin Saleem أبو سلمة الحمصي; al-Hasan bin Swar الحسن بن سوار; Auf bin Malik bin Nadlah عوف بن مالك بن نضلة - أبو الأحوص; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Isma'il bin 'Abdullah bin 'Abdullah إسماعيل بن عبد الله بن عبد الله بن أويس; Isma'il bin Abi Khalid al-Ahmsi إسماعيل بن أبي خالد الأحمسي; Yahya bin Jabir al-Tai'i يحيى بن جابر الطائي (Sunan Abi Dawud)
Ibn ‘Umar reported the Messenger of Allah (May peace be upon him)As saying: The Muslims will soon be besieged up to Madina so that their most distant frontier outpost will be Salah.
Grade: Sahih

Hadith #4319 - Sunan Abi Dawud - al-Nawas bin Sam'an al-Kalabi; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Safwan bin Salah bin Safwan صفوان بن صالح بن صفوان; Yahya bin Jabir al-Tai'i يحيى بن جابر الطائي (Sunan Abi Dawud)
The Prophet (ﷺ) said: Let him who hears of the Dajjal (Antichrist) go far from him for I swear by Allah that a man will come to him thinking he is a believer and follow him because of confused ideas roused in him by him.
Grade: Sahih